Waterfront, Pelestarian Cagar Bu ANALISIS KENYAMANAN SPASIAL DAN FASILITAS LANSKAP PADA KAWASAN WATERFRONT BENTENG KUTO BESAK PALEMBANG - Zehrina Saputri; Zaskia Sela Sapitri; Nadine Zabarij Yaqutah; Nurjannah; Nayla Tiara Mufidah; Malikin Gofur; Listen Prima; Sri Lilianti Komariah (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: Traditional architecture as a tangible cultural heritage asset requires dynamic preservation efforts through protection, development, and utilization to maintain its existence and enhance its value for future generations. The identity of Palembang as a Water City, recognized since the era of the Palembang Darussalam Sultanate, is reflected in the presence of the Musi River and Benteng Kuto Besak as significant historical and cultural elements. However, the Waterfront area of Benteng Kuto Besak and its surroundings has not been optimally managed as a historic district and as part of Palembang’s urban development. In fact, the Musi River waterfront holds substantial potential in economic, cultural, historical, and sustainable tourism aspects. This study aims to analyze the role of the Musi River waterfront around Benteng Kuto Besak in enhancing sustainable tourism in Palembang through a heritage preservation approach and the strengthening of city identity. In addition, structural considerations are addressed through the use of steel sheet pile foundations with a diameter of 500 mm and a length of 22 m, designed based on allowable stress and loading factors, including seismic forces, to ensure safety and long-term sustainability of the riverside area. Keyword : Waterfront, Cultural heritage Preservation, Foundation Abstrak: Arsitektur tradisional sebagai bagian dari benda cagar budaya bersifat kebendaan memerlukan pelestarian yang dinamis melalui upaya perlindungan, pengembangan, dan pemanfaatan guna mempertahankan keberadaan serta meningkatkan nilainya bagi generasi mendatang .Zain, Zairin (2014) Identitas Kota Palembang sebagai Kota Air yang telah dikenal sejak masa Kesultanan Palembang Darussalam tercermin pada keberadaan Sungai Musi dan Benteng Kuto Besak sebagai elemen sejarah dan budaya yang penting. Namun, kawasan Waterfront Benteng Kuto Besak dan sekitarnya belum dikelola secara optimal sebagai kawasan bersejarah dan bagian dari pengembangan kota. Firmansyah, K. G. S. (2000) Padahal, kawasan Waterfront Sungai Musi memiliki potensi besar dalam aspek ekonomi, budaya, sejarah, dan pariwisata berkelanjutan. Penelitian ini bertujuan menganalisis peran waterfront Sungai Musi di sekitar Benteng Kuto Besak dalam meningkatkan pariwisata berkelanjutan di Kota Palembang melalui pendekatan pelestarian kawasan bersejarah dan penguatan identitas kota. Robi 2025.Selain itu, kajian teknis struktur turut diperhatikan melalui penggunaan pondasi tiang turap baja berdiameter 500 mm dengan panjang 22 m yang dirancang mempertimbangkan tegangan izin dan faktor pembebanan, termasuk gaya gempa, guna menjamin keamanan dan keberlanjutan kawasan tepi sungai.Vembri Affianto, (2007) Rizky Dendy (2007) Kata Kunci : Waterfront, Pelestarian Cagar Budaya, Pondasi